Diabetic Ketoacidosis Elicits Systemic Inflammation Associated with Cerebrovascular Endothelial Cell Dysfunction. (9th August 2013) - Close, Taylor E.; Cepinskas, Gediminas; Omatsu, Tatsushi; Rose, Keeley L.; Summers, Kelly; Patterson, Eric K.; Fraser, Douglas D.
Abstract Objective To determine if the DKA‐induced inflammation in juvenile mice provokes activation and dysfunction of CVECs. Methods DKA in juvenile mice was induced with administration of STZ and ALX. Blood from DKA mice was assessed for cytokines and soluble cell adhesion proteins, and either DKA plasma or exogenous compounds were applied to immortalized bEND3. Results DKA increased circulating levels of IL‐6, IL‐8(KC), MCP‐1, IL‐10, sE‐selectin, sICAM‐1, and sVCAM‐1. Stimulation of bEND3 with DKA plasma caused cellular activation (increased ROS and activation of NF‐κΒ), upregulation of a proadhesive phenotype (E‐selectin, ICAM‐1, and VCAM‐1), and increased leukocyte‐bEND3 interaction (leukocyte rolling/adhesion). TEER, a measure of bEND3 monolayer integrity, was decreased by DKA plasma. Activation and dysfunction of bEND3 with DKA plasma were suppressed by plasma heat treatment (56°C, 1 hour) and replicated with the application of DKA recombinant cytomix (IL‐6, IL‐8[KC], MCP‐1, and IL‐10), implicating circulating inflammatory protein(s) as mediators. Treatment of bEND3 with β‐OH‐butyrate, the main ketone elevated in DKA, failed to mimic the DKA plasma–induced activation and dysfunction of bEND3. Conclusions DKA elicits systemic inflammation associated with CVEC activation and dysfunction, possibly contributing to DKA‐associated intracranial microvascular complications.